PENGEMBANGAN BAHAN AJAR BERBASIS PROBLEM BASED LEARNING BERBANTUAN LINKTREE UNTUK MENINGKATKAN KEMAMPUAN KERJASAMA MAHASISWA UNIVERSITAS ALMUSLIM BIREUEN - Novi Sari Liani; Fatimah; Novianti; Intan Wulan Sari; M.Taufiq (LPPM Universitas Cipta Mandiri, 2025)
This study aims to develop teaching materials based on the problem-based learning model, using linktree, to improve the collaboration skills of Umuslim Bireun students and to test their feasibility. This study employed a quantitative approach with Research and Development (R&D) methods. The ADDIE development model utilized analysis, design, development, implementation, and evaluation. The results of the media expert validation showed that the media aspects, technical quality, and media size achieved percentage scores of 83.53%, 87.92%, and 90.85%, respectively, resulting in a very good conclusion. The material expert analysis clearly demonstrated that the media coverage, accuracy, currency, and arousal of interest achieved percentage scores of 86.73%, 88.53%, 92.30%, 93.72%, and 90.81%, respectively, resulting in a very good conclusion. The results of the analysis of linguists clearly show that in terms of clarity, suitability with student development and suitability with language rules with a presentation value of 86.36%, 92.87%, 93.75%. The results of the overall feasibility test for individual, group and field validation with a percentage of 87%, 90% and 93% are very qualified. The results of the gain normality test analysis obtained a result of 0.88 so that it can be concluded that there is an increase in the ability of Umuslim students to cooperate with teaching materials based on the problem based learning model assisted by linktree.